Inside epoxyeicosatrienoic acids and cardiovascular disease - Tacconelli, Stefania; Patrignani, Paola (Frontiers in Pharmacology, 2014)
Epoxyeicosatrienoic acids (EETs) generated from arachidonic acid through cytochrome P450 (CYP) epoxygenases have many biological functions. Importantly, CYP epoxygenase-derived EETs are involved in the maintenance of cardiovascular homeostasis. In fact, in addition to their potent vasodilating effect, EETs have potent anti-inflammatory properties, inhibit platelet aggregation, promote fibrinolysis, and reduce vascular smooth muscle cell proliferation. All EETs are metabolized to the less active dihydroxyeicosatrienoic acids (DHETs) by soluble epoxide hydrolase (sEH). Numerous evidences support the role of altered EET biosynthesis in the pathophysiology of hypertension and suggest the utility of antihypertensive strategies that increase CYP-derived EET or EET analogs. Indeed, a number of studies have demonstrated that EET analogs and sEH inhibitors induce vasodilation, lower blood pressure and decrease inflammation. Some of these agents are currently under evaluation in clinical trials for treatment of hypertension and diabetes. However, the role of CYP epoxygenases and of the metabolites generated in cancer progression may limit the use of these drugs in humans.